The relationship of high sensitivity C-reactive protein to percent body fat mass, body mass index, waist-to-hip ratio, and waist circumference in a Taiwanese population - Lin Wen-Yuan; Lai Ming-May; Liu Chiu-Shong; Li Chia-Ing; Kardia Sharon LR; Lin Cheng-Chieh; Chang Pei-Chia; Lee Yih-Dar; Chen Ching-Chu; Lin Chih-Hsueh; Yang Chuan-Wei; Hsiao Chih-Yi; et al. (BMC, 2010)
Abstract Background High-sensitivity C-reactive protein (hs-CRP) is an easily measured inflammatory biomarker. This study compared the association of percent body fat mass (%FM), body mass index (BMI), waist circumference (WC), and waist-to-hip ratio (WHR) with hs-CRP in a Taiwanese population. Methods A total of 1669 subjects aged 40-88 years were recruited in 2004 in a metropolitan city in Taiwan. The relationships between obesity indicators and a high level of hs-CRP were examined using multivariate logistic regression analysis. The upper quartile of the hs-CRP distributions was defined as the high category group. The areas under the curve (AUCs) of the receiver operating characteristic curves were calculated for all obesity indicators to compare their relative ability to correctly classify subjects with a high level of hs-CRP. Results After multivariate adjustment, the odds ratio for %FM was the only significant indicator that was associated with a high level of hs-CRP in men (1.55, 95% CI: 1.07-2.25). All indicators were associated with a high level of hs-CRP in women. In men, the AUCs for %FM were significantly higher than those for BMI, WHR, and WC, when demographic and lifestyle behaviors were considered (p < 0.001 for all comparisons), but they were not significantly different in females. Conclusions Our study demonstrates that %FM is the only obesity indicator that is strongly associated with a high level of hs-CRP after adjusting for sociodemographic factors, lifestyle behaviors and components of metabolic syndrome in both genders in a Taiwanese population aged forty years and over. In men, %FM had the greatest ability to classify subjects with a high level of hs-CRP when only demographic and lifestyle behaviors were considered. Our study finding has important implications for the screening of obesity in community settings.